(untitled) (Research, Society and Development, 2021)
Due to the need to analyze the occurrence of the number of teachers who get sick for various reasons in schools in Brazil, this study aims to catalog the Stricto Sensu academic productions listed in the Coordination for the Improvement of Higher Education Personnel (Capes) and that address the Faculty illness theme. The purpose of the survey was to elaborate a quantitative overview of scientific production and analyze the number of publications that investigated this theme in the last thirteen years. The research is characterized as a bibliographic study with a quantitative approach. The survey was carried out using the descriptor school illness in quotation marks, with the filters dissertations and theses in the period from 2007 to 2020. The study recorded a total of thirty-five scientific productions with this theme, with five studies classified in the Master’s mode Professional, twenty-two academic Master’s dissertations and eight Doctoral theses. The data revealed that the year 2015 was the period with the highest concentration of this theme with eight incidences of research in the field, followed by the year 2017, which showed six occurrences. On average, this theme registered 2.5 incidence per year throughout the time series, demonstrating a small Srito Sensu production on the theme in Brazil. However, it is noteworthy that a dissertation or master’s thesis can generate at least 2 to 3 academic articles.